Living Labs for People (LL4P): A transdisciplinary approach to facilitating innovation processes from the ground - Habermann, Birgit (International Livestock Research Institute, 2024)
CGIAR Research Initiative on “Low-emission Food Systems (Mitigate+)” WP3 on Living Labs for People 8 AM –9:30 AM EST, December 9, 2024. Zoom meeting